2020
DOI: 10.1186/s12935-020-01437-y
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA hsa_circRNA_0001776 inhibits proliferation and promotes apoptosis in endometrial cancer via downregulating LRIG2 by sponging miR-182

Abstract: Background Endometrial cancer (EC) is a common malignancy of the female reproductive system. Circular RNAs (circRNAs) were demonstrated to exert critical roles in cancers, including EC. This study aimed to investigate the effects of hsa_circRNA_0001776 (circ_0001776) on EC. Methods Real-time quantitative PCR (RT-qPCR) was used to measure circ_0001776, microRNA-182 (miR-182) and leucine-rich repeats and immunoglobulin-like domains 2 (LRIG2) expression. The diagnostic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Similarly, Jia et al reported that LRIG2, a tumor suppressor gene mainly expressed in the ovaries and uterus, contain a putative binding site for miR-182 [140]. As a result, overexpression of miR-182 in EC overrides the inhibitory effects of LRIG2 on cell growth and the glycolytic metabolism [47].…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Jia et al reported that LRIG2, a tumor suppressor gene mainly expressed in the ovaries and uterus, contain a putative binding site for miR-182 [140]. As a result, overexpression of miR-182 in EC overrides the inhibitory effects of LRIG2 on cell growth and the glycolytic metabolism [47].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, circ_0001776 also regulated the expression of LRIG2 by acting as a sponge for miR-182, and CIRC_0001776 inhibited EC progression through miR-182/LRIG2 axis. 11 , 131 …”
Section: Circular Rnas and Endometrial Cancer (Ec)mentioning
confidence: 99%
“…In other words, circ_0001776 inhibits the occurrence and development of EC through miR-182/LRIG2 axis, providing a potential target for the treatment of EC. 131 …”
Section: Circular Rnas and Endometrial Cancer (Ec)mentioning
confidence: 99%
“…Circular RNAs (circRNAs/circ), a novel class of non-coding RNAs (ncRNAs), are characterized by a covalently closed loop without a 5 cap and 3 polyadenylated tail, and are generated through abnormal transcription and splicing ( 6 ). Accumulating evidence has demonstrated that circRNAs exert effects on multiple biological and pathological processes, suggesting that they may be involved in the occurrence and development of numerous diseases, including cancer ( 7 , 8 ). For example, circ-acetyl-CoA carboxylase α (ACACA) has been previously reported to promote the proliferation of non-small cell lung cancer (NSCLC) cells by modulating proliferation, migration and glycolysis via microRNA (miRNA/miR)-1183 and the PI3K/AKT signaling pathway ( 9 ).…”
Section: Introductionmentioning
confidence: 99%